Stability Analysis of θ-Methods for Neutral Multidelay Integrodifferential System - Y. Xu; J. J. Zhao; Z. N. Sui (Discrete Dynamics in Nature and Society)
This paper studies the stability of a class of neutral delay integrodifferential system. A necessary and sufficient condition of stability for its analytic solutions is considered. The improved θ-methods are developed. Some numerical stability properties are obtained and numerical experiments are given.